Friction modeling of multi-walled carbon nanotubes for material damping application - Cheong, Candy. (2011)
Damping is an important design element that cannot be taken lightly. This is especially true when system has to overcome vibrations to ensure the safety of the user or the general public. In view of the importance to establish a good damping system, exploring of new materials would be the first step to achieve an enhancement to the existing models. In this report, we looked into the potential of using carbon nanotubes fillers to inject damping into composite structures. Carbon nanotubes are chosen because of their excellent mechanical properties such as high strength and high Young’s modulus. In order to investigate the possibility of using carbon nanotubes as reinforcement for composites, a model was developed. An ideal model, whereby the alignments of the dispersed doubled-walled carbon nanotubes are assumed to be in the axial direction, is used to determine the composite system’s damping characteristics. In the vibration analysis, the force-displacement relationships of the model are broken down into 3 cases. Case 1 is when there is no interfacial slip, Case 2 when there are interfacial slips between resin and nanotubes and between nanotubes themselves and Case 3 when there is interfacial slip between resin and nanotubes. Making use of the proposed model, a series of numerical simulations are conducted to predict the damping loss factor of carbon nanotube-based composite. It is found out the as the strain level increase, the damping loss factor also increases. Parameter studies have also shown that by designing the system using resin with small Young’s modulus, high volume fraction of carbon nanotubes and low critical shear stress between nanotubes can yield an optimal damping result. For instance, with an extremely low volume fraction of 1%, the damping loss factor can be as high as approximately 30%. On the other side, it is important to note that designing the parameters as such can also lead to problems like incurring more cost due to high volume fraction used. Furthermore, a realistic model is also developed so as to compare the overall damping loss factor with the ideal model. The difference between the ideal and practical model is the characteristics of the randomly oriented carbon nanotubes. From the results, the overall damping loss factor is lower for the practical model and this is chiefly due to the lower damping capacity exhibit by the angled carbon nanotubes.